Effect of LSMC Implementation on Contractor Performance for National Road Construction In Aceh, Indonesia - Alfa Taras Bulba; Anita Rauzana (CV. Media Digital Publikasi Indonesia, 2023)
Performance Based Contract (PBC) which is used to replace traditional contracts in national road constructions in Indonesia has been improvised into the Long Segment Maintenance Contract (LSMC). Contractor role and risk influence contractor performance; hence, the LSMC was introduced to assist contractors in improving their organizations to enhance performance in undertaking national road construction projects. This study was conducted to investigate the relationship between LSMC and contractor performance in Aceh, Indonesia, with operational capabilities as the mediator. Data collection for this study was done through a questionnaire survey, which was carried out involving non-small contractor companies from grades 5 to 7. Questionnaires were sent to 104 respondents. From the 104 questionnaires disseminated, 100 were completed and deemed usable. The data were analysed by the PLS software, followed by SPSS. The findings showed a positive relationship between LSMC and contractor performance